2009
DOI: 10.1097/mpg.0b013e3181b7f563
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Gastroesophageal Reflux Clinical Practice Guidelines: Joint Recommendations of the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN)

Abstract: is an expert in gastroesophageal reflux disease and aerodigestive disorders. Yvan Vandenplas MD, PhD: YV is an expert in gastroesophageal reflux disease. Maartje Singendonk MD: MS is an expert in esophageal physiology. Michael Cabana MD: MC is a pediatrician with expertise in consensus guideline Carlo Di Lorenzo MD: CD is an expert in pediatric motility disorders and gastroesophageal reflux disease Frederic Gottrand MD: FG is an expert in esophagitis and gastroesophageal reflux disease Sandeep Gupta MD: SG is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
807
3
88

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(934 citation statements)
references
References 721 publications
9
807
3
88
Order By: Relevance
“…MII/pH is superior to pH monitoring alone for the evaluation of a temporal relation between symptoms and reflux episodes. 3,4 In children, proton pump inhibitors (PPIs) have been shown to be effective and safe for short-term treatment of erosive esophagitis and GERD symptoms that are refractory to other drugs. 4,5 Studies in adults and children have reported that in comparison with H2-receptor antagonists (H2RAs), PPIs results in higher and faster rates of healing of erosive esophagitis compared with H2RAs.…”
Section: Introductionmentioning
confidence: 99%
“…MII/pH is superior to pH monitoring alone for the evaluation of a temporal relation between symptoms and reflux episodes. 3,4 In children, proton pump inhibitors (PPIs) have been shown to be effective and safe for short-term treatment of erosive esophagitis and GERD symptoms that are refractory to other drugs. 4,5 Studies in adults and children have reported that in comparison with H2-receptor antagonists (H2RAs), PPIs results in higher and faster rates of healing of erosive esophagitis compared with H2RAs.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes were analyzed after a median of 39 days on PPI therapy, which coincides with the expected PPI efficacy time frame of ~4 weeks. 4 These pilot data also suggest the potential for improved safety with GGD of PPIs, as there were fewer adverse effects in the GGD arm compared with the CD arm. We detected a significant difference in the total score of the SN-5 questionnaire between arms ( Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…According to literature, GER is not the most frequent cause of apnea or apparent life-threatening events (ALTEs), but when this possibility is considered, it is advisable to carry out a prolonged esophageal pH monitoring study with polysomnography and, when available, multichannel intraluminal esophageal impedanciometry. 4,14,[18][19][20][21][22][23] Literature regarding the association of GERD with apnea, respiratory pauses, ALTE, or sudden infant death is very conflictive. This could be explained by the different criteria used to define respiratory arrest and the different methods of reflux evaluation, as well as the different populations.…”
Section: Discussionmentioning
confidence: 99%
“…14 When used in highly select cases, reflux was clearly associated with central and obstructive pathological apneas, but none of these studies has conclusively shown the relationship of cause and effect between GER and pathological apnea. 4,14,[18][19][20][21] To define a high RI for infants we used parameters used in many other studies. 15 RI higher than 10% was found in 45% of the infants in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation